Strong Oceanic Forcing on Decadal Surface Temperature Variability Over Global Ocean - Gu, Peng; Liu, Zhengyu; Delworth, Thomas L. (Geophysical research letters, 2024)
Sea surface temperature (SST) variability on decadal timescales has been associated with global and regional climate variability and impacts. The mechanisms that drive decadal SST variability, however, remain highly uncertain. Many previous studies have examined the role of atmospheric variability in driving decadal SST variations. Here we assess the strength of oceanic forcing in driving decadal SST variability in observations and state‐of‐the‐art climate models by analyzing the relationship between surface heat flux and SST. We find a largely similar pattern of decadal oceanic forcing across all ocean basins, characterized by oceanic forcing about twice the strength of the atmospheric forcing in the mid‐ and high latitude regions, but comparable or weaker than the atmospheric forcing in the subtropics. The decadal oceanic forcing is hypothesized to be associated with the wind‐driven oceanic circulation, which is common across all ocean basins. Plain Language Summary Decadal variabilities in SST create large climate responses, ranging from heat waves to droughts to enhanced hurricanes. However, there has been considerable uncertainty over whether decadal SST variations are driven primarily by atmospheric forcing or ocean forcing related to ocean circulation. Using a newly developed theoretical framework, we provide the first quantitative estimation of decadal oceanic forcing across the global ocean in observations and state‐of‐the‐art climate model. Our estimation shows that decadal ocean forcing is stronger than the atmospheric forcing by about 2–3 times in the mid‐ and high latitude, but comparable or even weaker than atmospheric forcing in the subtropics. Key Points In the mid‐ and high latitude, decadal oceanic forcing is stronger than atmospheric forcing by about 2–3 times across world ocean basins In the subtropics, decadal oceanic forcing is comparable to or even weaker than atmospheric forcing Decadal oceanic forcing is likely contributed predominantly by the wind‐driven oceanic circulation